Extr. du livre : Etty Hillesum, une lecture juive, Note sur le messie Lecture d’Isaïe 53 - Cohen, Monique Lise (Revue CMC Review, 2019)
The essay applies a biblical text, Isaiah 53, to a declaration by Etty Hessum, interned by the Nazis in 1942, “On voudrait être un baume versé sur tant de plaies” / “One would like to be a balm applied to so many wounds,” referencing the Messiah.